Analisis Faktor-Faktor yang Memengaruhi Persepsi Masyarakat Terhadap Wakaf Uang di Kota Bandung - Cupian Cupian; Nurun Najmi (Jurnal Ilmiah Ekonomi Islam, 2020)
Waqf is one of Islamic philanthropy that can develop the economy of ummah. Indonesia has a big waqf potential but in reality the waqf assets are unproductive. One of development action to put waqf assets to good use is by applying cash waqf. But the realization of cash waqf collection is still far from of the existing potential. It is caused by the low literacy of the public about the cash waqf, hencemost of the waqf assets is utilized as mosques, tombs and other immovable property. The aim of this research is to describe respondent characteristics and to analyze factors that affecting people’s perception on cash waqf. This research was conducted in Bandung city uses 100 respondents who ever or never give cash waqf. The data is obtained by using questioner in ordinal scale and likert. This research uses a descriptive quantitative approach. Data analyzing conducted bydoing validity test and realibility test using binary logistic regression analyzingis conducted for determining factor that influence citizen perception of cash waqf. The result shows people’s perception on cash waqf is significantly influenced by internal factor namely comprehension about cash waqf and external factor namely cash waqf convenience.